Treatment and rehabilitation for cervical cancer: the experience of patient journey management - A. A. Akavova; A. G. Solopova; D. V. Blinov; E. E. Achkasov; V. N. Galkin; D. I. Korabelnikov; A. N. Mnatsakanyan; D. A. Petrenko; G. K. Bykovshchenko; P. L. Khazan (IRBIS LLC, 2023)
Radical surgical intervention, chemoradiotherapy and immune therapy implicated for patients with cervical cancer (CC) can result in significant morphofunctional, psychological, sexual disorders and social maladjustment. To optimize treatment and rehabilitation for CC patients, a routing approach has been established. This approach involves the patient's journey during diagnosis and treatment with well-defined timed stages. Additionally, a rehabilitation program with lifelong follow-up has been implemented. Prior to commencing therapy, undertaking rehabilitation after oncogynecological treatment during the stage spanning from diagnosis to therapy initiation contributes to enhancing the quality of life (QoL) for CC patients.